Combustion and Performance Evaluation of a Spark Ignition Engine Operating with Acetone–Butanol–Ethanol and Hydroxy (2021)
Alternative fuels for internal combustion engines (ICE) emerge as a promising solution for a more sustainable operation. This work assesses combustion and performance of the dual-fuel operation in the spark ignition (SI) engine that simultaneously integrates acetone–butanol–ethanol (ABE) and hydroxy (HHO) doping. The study evaluates four fuel blends that combine ABE 5, ABE 10, and an HHO volumetric flow rate of 0.4 LPM. The standalone gasoline operation served as the baseline for comparison. We constructed an experimental test bench to assess operation conditions, fuel mode, and emissions characteristics of a 3.5 kW-YAMAHA engine coupled to an alkaline electrolyzer. The study proposes thermodynamic and combustion models to evaluate the performance of the dual-fuel operation based on in-cylinder pressure, heat release rate, combustion temperature, fuel properties, energy distribution, and emissions levels. Results indicate that ABE in the fuel blends reduces in-cylinder pressure by 10–15% compared to the baseline fuel. In contrast, HHO boosted in-cylinder pressure up to 20%. The heat release rate and combustion temperature follow the same trend, corroborating that oxygen enrichment enhances gasoline combustion. The standalone ABE operation raises fuel consumption by around 10–25 g • kWh−1 compared to gasoline depending on the load, whereas HHO decreases fuel consumption by around 25%. The dual-fuel operation shows potential for mitigating CO, HC, and smoke emissions, although NOx emissions increased. The implementation of dual-fuel operation in SI engines represents a valuable tool for controlling emissions and reducing fuel consumption while maintaining combustion performance and thermal efficiency